From semi-hard processes to the unintegrated gluon distribution: a phenomelogical path in the high-energy framework - Bolognino, Andrèe Dafne; Cipparrone, Gabriella; Papa, Alessandro (Università della Calabria, 2021)
The class of semi-hard reactions represents a promising venue where to enhance our knowledge of strong interactions and deepen the aspects related to this theory in kinematical regimes so far unexplored. In particular, the high energies reached in electron-proton and in proton-proton collisions first at HERA and then at the LHC, allow us to study scattering amplitudes of hard and semi-hard processes in perturbative QCD. The structure of this thesis can be considered twofold. On one hand, the possibility to distinguish those channels where at least two final-state particles are emitted with large separation in rapidity and with an untagged system, permits to test the BFKL dynamics as resummation energy logarithms in the t-channel. Indeed, these inclusive reactions occur in the Regge limit, s jtj, and fixed-order calculations in perturbative QCD miss the effects of energy logarithms, which are so large to compensate the smallness of the strong coupling constant and must be resummed order by order in perturbation theory. The most powerful theoretical tool to provide the resummation of terms proportional to powers of these logarithms is the Balitsky- Fadin-Kuraev-Lipatov (BFKL) approach. In this framework, the hadroproduction of two forward jets with high transverse momenta separated by a large rapidity at the LHC, known as Mueller–Navelet jets process, has been one of the most investigated reactions. With the idea of deepening our understanding of the BFKL formalism, a new channel belonging to the semi-hard processes category is proposed: the inclusive production of a light charged hadron and a jet with high transverse momentum widely separated in rapidity, whose calculation is performed at NLO accuracy. The importance of this process relies in the possibility to probe a complementary region to one analyzed for the Mueller–Navelet jets. Hadrons, indeed, can be tagged at much smaller values of the transverse momentum than jets. It is proved how asymmetric cuts for the transverse momentum (naturally occurring because the final state is featured by objects of different nature) enhance the BFKL effects and how it is possible to discriminate between different parametrizations of fragmentation functions for the hadron in the final state. Additionally, another reaction is proposed: the hadroproduction of heavy-quark pairs well separated in rapidity. On the other hand, also the class of processes featured by the detection of a single forward object in lepton-proton collision can provide us useful ingredients to develop intriguing phenomenological studies. In particular, the exclusive leptoproduction of light vector mesons, r and f, is exhaustively investigated. In this context, the study of helicity-dependent observables allows us to discriminate among several unintegrated gluon distribution models, whose original definition naturally encodes the BFKL-equation evolution dynamics. This kind of parton density allows us to get access to the hadronic structure at small-x.
Dottorato di ricerca in scienze e tecnologie fisiche, chimiche e dei materiali, Ciclo XXXIII
Keywords: high-energy physics; semihard reactions; unintegrated gluon distributions; BFKL formalism; phenomenology; Research Subject Categories::NATURAL SCIENCES::Physics